PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN PENDEKATAN KONTEKSTUAL SISWA KELAS V - Tessa Dety Arizna; Elfia Sukma; Mai Sri Lena (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this research was to describe the improvement of narrative writing skill by Contextual Approachin the fifth grade of elementary school. Types of using research was classroom action research with qualitative and quantitative approach. The research procedure consistend of planning, acting, observing, and reflecting. The research subject was 30 grade. The result of the study showed the average of students result: a) First Cycle in pre-writing 91.1, the writing 63.2, post-writing 62.7, teachers activity 72.7% and students activity  63.6%, b) Second Cycle in pre-writing 94.7, the writing 73.5, post-writing 80.7, teachers activity 95.5% and students activity 95.5%. The conclusions from the result of the research conducted are using the contextual approach could improve the naration writing skills of students in class V SDN 26 Air Tawar Timur Padang City.  Keywords : Narrative Essay, Contextual Approach, Elementary School